Coordination of the in situ payload of Solar Orbiter - Walsh,AP; Horbury,TS; Maksimovic,M; Owen,CJ; Rodriguez-Pacheco,J; Wimmer-Schweingruber,RF; Zouganelis,I; Anekallu,C; Bonnin,X; Bruno,R; Carrasco,Blazquez I; Cernuda,I; et al. (Astronomy and Astrophysics: a European journal, 2020)
Solar Orbiter’s in situ coordination working group met frequently during the development of the mission with the goal of ensuring that its in situ payload has the necessary level of coordination to maximise science return. Here we present the results of that work, namely how the design of each of the in situ instruments (EPD, MAG, RPW, SWA) was guided by the need for coordination, the importance of time synchronisation, and how science operations will be conducted in a coordinated way. We discuss the mechanisms by which instrument sampling schemes are aligned such that complementary measurements will be made simultaneously by different instruments, and how burst modes are scheduled to allow a maximum overlap of burst intervals between the four instruments (telemetry constraints mean different instruments can spend different amounts of time in burst mode). We also explain how onboard autonomy, inter-instrument communication, and selective data downlink will be used to maximise the number of transient events that will be studied using high-resolution modes of all the instruments. Finally, we briefly address coordination between Solar Orbiter’s in situ payload and other missions.